Speculation on OTTV Value in Buildings With Predominance of Concrete Cladding in Humid Tropical Areas: Case Study: Tree Inn Hotel in Batu - Biyantoro, Anjas; Bonifacius, Nurhamdoko; Poerwoningsih, Dina (Proceedings of International Conference of Graduate School on Sustainability, 2025)
One initiative that can be implemented involves formulating an architectural sustainability paradigm that is conscious and responsive to energy conservation. The use of energy for cooling buildings is a crucial factor in global energy consumption. The envelope of a building, which encompasses its walls, windows, and roof, plays a crucial role in determining the building’s thermal performance. The Overall Thermal Transmittance Value (OTTV) is a parameter used to measure external heat gain through the building envelope. High OTTV values can increase the energy consumption of buildings, especially in the cooling system. The primary objective of this study is to evaluate the impact of OTTV on the building envelope, with the aim of promoting energy conservation. By understanding the value of OTTV, this study will analyze and relate it to the design of buildings dominated by concrete, which resembles the trunk of a giant tree, and assess whether it will have a significant heat gain. This research is quantitative and will be conducted using both simulation and experimental methods. The results of this study will also inform guidelines for designing energy-efficient buildings based on national standards, such as SNI 6389-2020. This research will be carried out in several stages, namely selecting a specific building as a case, identifying dimensional and material specifications, Data Collection, Data Analysis, and Conclusion. This research is expected to provide a clear picture of how to analyze the OTTV value on the building envelope for energy conservation, especially at the Tree Inn Hotel located in Batu Tourism City. Because the Tree Inn Hotel building has a specific building envelope, the envelope consists of a concrete blanket on one side, whereas the opposite side does not utilize a concrete blanket envelope.